Preview effects of plausibility and character order in reading Chinese transposed words: evidence from eye movements. (19th March 2013) - Yang, Jinmian
Abstract : The current paper examined the role of plausibility information in the parafovea for Chinese readers by using two‐character transposed words (in which the order of the component characters is reversed but are still words). In two eye‐tracking experiments, readers received a preview of a target word that was (1) identical to the target word, (2) a reverse word that was the target word with the order of its characters reversed or (3) a control word different from the target word. Reading times on target words were comparable between the identical and the reverse preview conditions when the reverse preview words were plausible. This plausibility preview effect was independent of whether the reverse word shared the meaning with the target word or not. Furthermore, the reverse preview words yielded shorter fixation durations than the control preview words. Implications of these results for preview processing during Chinese reading are discussed.